Comparative Studies on Cellular Behaviour of Carnation (Dianthus caryophyllus Linn. cv. Grenadin) Grown In Vivo and In Vitro for Early Detection of Somaclonal Variation - Jamilah Syafawati Yaacob; Rosna Mat Taha; Arash Khorasani Esmaeili (The Scientific World Journal)
The present study deals with the cytological investigations on the meristematic root cells of carnation (Dianthus caryophyllus Linn.) grown in vivo and in vitro. Cellular parameters including the mitotic index (MI), chromosome count, ploidy level (nuclear DNA content), mean cell and nuclear areas, and cell doubling time (Cdt) were determined from the 2 mm root tip segments of this species. The MI value decreased when cells were transferred from in vivo to in vitro conditions, perhaps due to early adaptations of the cells to the in vitro environment. The mean chromosome number was generally stable (2n=2x=30) throughout the 6-month culture period, indicating no occurrence of early somaclonal variation. Following the transfer to the in vitro environment, a significant increase was recorded for mean cell and nuclear areas, from 26.59 ± 0.09 μm2 to 35.66 ± 0.10 μm2 and 142.90 ± 0.59 μm2 to 165.05 ± 0.58 μm2, respectively. However, the mean cell and nuclear areas of in vitro grown D. caryophyllus were unstable and fluctuated throughout the tissue culture period, possibly due to organogenesis or rhizogenesis. Ploidy level analysis revealed that D. caryophyllus root cells contained high percentage of polyploid cells when grown in vivo and maintained high throughout the 6-month culture period.